Penambahan Instruksi pada Tahapan Regulation Model Discovery Learning sebagai Upaya Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - Alfina Dewanty; Maridi Maridi; Sri Widoretno (Universitas Sebelas Maret, 2017)
The research aims to increase the ability for finding and connecting concept by addition instruction of regulationstage discovery learning. This research is a Classroom Action Research with 2 cycles. Procedure of researchincludes planning, acting, observing, and reflecting. Subject of this research is 11 male students senior highschool and 25 female students senior high school. Data collection with observation, interview, documentation,and test for measure score of concept map. Data obtained in the form of answers and note that measured withconcept map based scoring in concept map expert. Data validation use technique of triangulation method. Dataanalysis conducted data reduction, presentation of data, and conclusion based descriptive qualitative analysis.Result of this research show range of students concept map scores on the pre-cycle 2,6-9% and average is 5,7%,with 18 students above average score. Concept map score on first cycle have range 6,2%-73,6% and average is31%, with 16 students above average score. Concept map score on second cycle have range 14,8-56,2% andaverage is 31,6%, with 21 students above average score, therefore the addition instruction of regulation stagediscovery learning increase the ability for finding and connecting concepts based on concept map score ofstudents from first cycle to second cycle.